PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DALAM MENINGKATKAN KREATIVITAS SISWA PADA MATERI BUMI DAN TATA SURYA - Jamratul Ula; Zulkarnaini Zulkarnaini; Syarifah Rahmiza Muzana; Rina Mirdayanti (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The research aims to enhance the creativity of students by applying the TSTS (Two Stay Two Stray) learning model at SMPN 2 Kuta Baro Aceh Besar. The sample in this study was a student of class VII C of 22 students. This research uses a pre-experimental research design. Creativity data is collected through the observation sheet with the Guttman scale. Analysis of data creativity is calculated using a percentage formula. The study results of the student's learning creativity at the initial observation were 54.5% being in the category quite creative and the final observation score was 82% with the category highly creative. It can be concluded that the application of the learning model of Two Stay Two Stray can enhance the creativity of students of grade VII C at SMPN 2 Kuta Baro on Earth and Solar System matter.